Awareness of Iron Deficiency Anemia among Women of Reproductive Age in Hubei Province, China - Hussain, Tabish; Shu, Li Yu (Asian Journal of Medical Sciences, 2010)
Objective: To assess the level of awareness about causes, prevention and treatment of iron deficiency anemia among women of reproductive age in Hubei province, a south eastern province of China. Method: Cross sectional study was conducted by using a self designed standardized pretested questionnaire in peripheral areas of Wuhan city, the capital of Hubei province from January 2009 to December 2009.Women aged 18-45 years without any previous history of medical or gynecological problems were recruited. Results: A total 385 women were surveyed for Iron Deficiency Anemia (IDA).77.9% women (n=300) were aware of the term IDA, with the highest proportion of 88.1% falling in age group 25-35 years. Most of the women were aware of the fact that their diet contains iron and its importance in health. Women who had children and of working class had greater knowledge about the iron deficiency anemia. Conclusion: Awareness regarding IDA is directly linked with the educational and social status of a community and is found to be increasing with the passage of time with exploration and accessibility to media and health care facilities. Women of younger ages are more concern about their own health and much careful about their expected babies in terms of nutritional facts as compared to the elder ladies. Keywords: Iron deficiency anemia; Reproductive age DOI: 10.3126/ajms.v1i1.2607 Asian Journal of Medical Sciences Vol.1(1) 2010 p.12-13